2007
DOI: 10.1029/2006gb002766
|View full text |Cite
|
Sign up to set email alerts
|

Air‐sea exchange in the global mercury cycle

Abstract: [1] We present results from a new global atmospheric mercury model coupled with a mixed layer slab ocean. The ocean model describes the interactions of the mixed layer with the atmosphere and deep ocean, as well as conversion between elemental, divalent, and nonreactive mercury species. Our global mean aqueous concentrations of 0.07 pM elemental, 0.80 pM reactive, and 1.51 pM total mercury agree with observations. The ocean provides a 14.1 Mmol yr À1 source of mercury to the atmosphere, at the upper end of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
275
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 225 publications
(290 citation statements)
references
References 67 publications
(145 reference statements)
13
275
2
Order By: Relevance
“…Increased volatilization of mercury from ocean and land reservoirs as a result of climate change would transfer mercury between ecosystems via atmospheric transport, re-depositing it in a more mobile and presumably more toxic form. Volatilization of mercury from the ocean is directly affected by warming (lower solubility of elemental mercury) and would also be affected by changes in ocean biology and circulation (Strode et al, 2007;Sunderland and Mason, 2007). Increased volatilization of soil mercury could potentially be of considerable importance, as the amount of mercury stocked in soil (1.2 Â 10 6 Mg) dwarfs that in the atmosphere (6 Â 10 3 Mg) and in the ocean (4 Â 10 4 Mg) (Selin et al, 2008).…”
Section: Effect Of Climate Change On Mercurymentioning
confidence: 99%
“…Increased volatilization of mercury from ocean and land reservoirs as a result of climate change would transfer mercury between ecosystems via atmospheric transport, re-depositing it in a more mobile and presumably more toxic form. Volatilization of mercury from the ocean is directly affected by warming (lower solubility of elemental mercury) and would also be affected by changes in ocean biology and circulation (Strode et al, 2007;Sunderland and Mason, 2007). Increased volatilization of soil mercury could potentially be of considerable importance, as the amount of mercury stocked in soil (1.2 Â 10 6 Mg) dwarfs that in the atmosphere (6 Â 10 3 Mg) and in the ocean (4 Â 10 4 Mg) (Selin et al, 2008).…”
Section: Effect Of Climate Change On Mercurymentioning
confidence: 99%
“…These observations also highlight that an assumed constant DGM concentrations in the modeling study may lead to substantial uncertainties of air/sea Hg(0) flux since the measurements presented the high temporal and spatial variation of DGM in surface waters. More reliable parameterization to describe the aquatic DGM production and consumption will significantly improve the modeling result (Strode et al, 2007;Soerensen et al, 2013).…”
Section: Air/sea Hg(0) Fluxmentioning
confidence: 99%
“…In seawater Hg can reduce to Hg(0) via photochemistry and microbial activities (Amyot et al, 1997;Rolfhus and Fitzgerald, 2004;Fantozzi et al, 2009;Qureshi et al, 2010;Whalin et al, 2007;Monperrus et al, 2007) from sea surface to atmosphere (Fitzgerald et al, 1984;Kuss and Schneider, 2007;Fu et al, 2010;Andersson et al, 2011;Ci et al, 2011a;Qureshi et al, 2012). Modeling studies showed that more than 80% of Hg deposited to oceans is reemitted to atmosphere as Hg(0) (e.g., Strode et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…gaseous elemental Hg and monomethyl Hg) or to operationally defined species based on laboratory analytical measurements such as total Hg (THg) and reactive Hg (Hg R ). [1][2][3] Table 1 summarises the abbreviations we use in this paper and their descriptions. This paper discusses the results from research conducted throughout the Arctic.…”
Section: Terminology Abbreviations and Location Informationmentioning
confidence: 99%